Can antineutrophil cytoplasmic antibody levels be used to inform treatment of pauci-immune vasculitis?. Issue 3 (May 2015) - Fussner, Lynn A.; Specks, Ulrich
<x xml:space="preserve">Abstract</x> Purpose of review The role of serial antineutrophil cytoplasmic antibody (ANCA) measurements to guide immunosuppressive therapy in pauci-immune vasculitis is an area of ongoing controversy. Evidence elucidating the relationship between ANCA levels and disease activity continues to grow. Recent findings The finding that proteinase 3-ANCA and myeloperoxidase-ANCA-associated diseases differ genetically has challenged the traditional classification and study of pauci-immune vasculitis. Multiple studies have also found that the clinical features and course of disease differ by ANCA antigen specificity more than clinical diagnosis. Advances in diagnostic assays and new techniques for the evaluation of ANCA levels over time have yielded improved assay performance in specific subsets of patients. In addition, increasing use of rituximab has added to our understanding of the relationship of ANCA levels to B-cell counts and disease relapse, which may differ by treatment regimen. Summary The relationship between ANCA levels and disease activity is impacted by multiple factors, including antigen specificity, disease manifestations, clinical assay, and therapeutic regimen. Each of these must be taken into account when determining the significance of ANCA levels during long-term follow-up of pauci-immune vasculitis.